ANALISIS KAPASITAS PROFIL GELAGAR MEMANJANG DAN GELAGAR MELINTANG TERHADAP GAYA-GAYA DALAM JEMBATAN RANGKA BAJA TIPE WARREN DENGAN MENGGUNAKAN SOFTWARE MIDAS CIVIL 2019 (Studi Kasus : Jembatan Penghubung Gedung RSCM Kencana – Gedung RSCM Kirana) - Arif, Muhammad Andi; Azhar, Moh.; Bangun, Sempurna; Naibaho, Pio Ranap Tua (Jurnal Ilmiah Global Education, 2023)
There are two access bridges that have different functions and to cross the Ciliwung river below as an access road from the RSCM Kencana building to RSCM Kirana. Where there is access to the bridge that is specifically for car/motorcycle riders and a special bridge for pedestrians. However, the density of motorists and pedestrians can hinder traffic access. Thus, supporting infrastructure was built, namely a vehicle bridge and connecting pedestrians from the Kencana RSCM building to the Kirana RSCM building. The type of bridge built is a concrete slab steel frame bridge. In this regard, this study aims to determine the values of the ultimate moment, shear, and axial forces that occur with the object viewed from the longitudinal and transverse girders whether they exceed the nominal profile value or not, and the deflections that occur on the behavior of the structure. on the bridge according to SNI 1725:2016 loading with the help of the MIDAS Civil 2019 software. From the results of the calculation and capital analysis on the MIDAS Civil 2019 software, the values of the internal forces on the object under review do not exceed the nominal strength value of the profile. First, the girder extends against ultimate moment of ϕMn ≥ Mu = 3.762,080 kNm ≥ 528,869 kNm, against shear force ϕVn ≥ Vu = 1.095,444 kN ≥ 909,282 kN, against axial compressive force ϕPn ≥ Pu = 8.532,876 k N ≥ 3.115,265 kN, to the axial tensile force ϕPn ≥ Pu 7.726,842 kN ≥ 2.434,744 kN. Second, the transverse girder with respect to the ultimate moment of ϕMn ≥ Mu = 1.242,046 kNm ≥ 53,723 kNm, against the shear force ϕVn ≥ Vu = 1.076,400 kN ≥ 81,513 kN, against the axial compressive force ϕPn ≥ Pu = 3.805,349 kN ≥ 255,812 kN. The deflection value that occurs at the ultimate state of the structural behavior of the bridge is 48.70 mm where this value is still smaller than the allowable deflection of 55 mm. So it can be concluded that the bridge structure is safe when it receives the ultimate load.